2013
DOI: 10.1007/s00221-013-3741-8
|View full text |Cite
|
Sign up to set email alerts
|

Human sensitivity to vertical self-motion

Abstract: Perceiving vertical self-motion is crucial for maintaining balance as well as for controlling an aircraft. Whereas heave absolute thresholds have been exhaustively studied, little work has been done in investigating how vertical sensitivity depends on motion intensity (i.e., differential thresholds). Here we measure human sensitivity for 1-Hz sinusoidal accelerations for 10 participants in darkness. Absolute and differential thresholds are measured for upward and downward translations independently at 5 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 43 publications
4
34
0
Order By: Relevance
“…To further investigate this effect, Figure 5 shows a linear relation ( R 2 = 0.65, p < 0.01) between the bias and precision across all participants and conditions. This effect, which follows Weber’s perceptual law (Fechner, 1860), is consistent with the signal dependence of (discrimination) precision that has been shown recently for vertical self-motion (Nesti et al, 2014). …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…To further investigate this effect, Figure 5 shows a linear relation ( R 2 = 0.65, p < 0.01) between the bias and precision across all participants and conditions. This effect, which follows Weber’s perceptual law (Fechner, 1860), is consistent with the signal dependence of (discrimination) precision that has been shown recently for vertical self-motion (Nesti et al, 2014). …”
Section: Resultssupporting
confidence: 90%
“…Studies conducted to characterize vestibular-only sensitivity are often performed in complete darkness or with closed eyes (Grabherr et al, 2008; MacNeilage et al, 2010a,b; Roditi and Crane, 2012; Valko et al, 2012; Nesti et al, 2014). However, the results of our free-fixation conditions suggest that, even under these circumstances, results could easily be influenced by vestibularly driven eye movements.…”
Section: Discussionmentioning
confidence: 99%
“…The "paternalistic vision hypothesis" of the gravity theory, which proposes that visual perception distorts the world according to the perceiver's abilities, has been strongly criticized recently 26 . An alternate interpretation for our finding is the possible differences in sensitivity to horizontal and vertical motions, and to the asymmetric sensitivity to upward and downward vertical motion 27,28 . The pioneering work of Fernandez & Goldberg 29 demonstrated that the utricular sensitivity to horizontal plane motion in monkeys was higher than the saccular sensitivity to vertical plane motion.…”
Section: Difference Between Verbal Reports and Blind Pullingmentioning
confidence: 68%
“…Thus, heading direction is monitored more robustly by integrating vestibular and visual signals, even when in conflict (Fetsch et al 2009;Butler et al 2015). Previous studies found differences in the representation of downward versus horizontal self-motion (Barnett-Cowan et al 2012;Nesti et al 2014). Moreover, functional magnetic resonance imaging (fMRI) showed that vertical visual self-motion activates a cerebral network including the parieto-insular vestibular cortex (PIVC), inferior parietal cortex, intraparietal sulcus, and cerebellar vermis (Indovina et al 2013b), a network known to process both visual and vestibular signals in humans (Indovina et al 2005;Lopez and Blanke 2011).…”
Section: Introductionmentioning
confidence: 97%